ANALISIS SENTIMEN ULASAN SHOPEE DI PLAY STORE DENGAN NAIVE BAYES: Sentiment Analysis of Shopee Reviews on the Play Store Using Naive Bayes - Muh Arfah Wahlil Pratama; Suriyadi Suriyadi; Nurjaya Nurjaya; Haldi Alfaisal; Melni Melni; Andi Nurwafia; Nurkhafitri Sahra; Asya Syara Marzan; Arman Rusdin; Dirgasari Dirgasari (Jurnal Komputer dan Teknologi, 2026)
This study evaluates user sentiments towards the Shopee application on the Google Play Store using a dataset of 1,000 crawled reviews. Preprocessing methods including cleaning, normalization, stopword filtering, and stemming were conducted, followed by feature weighting using TF-IDF. The classification model based on the Naive Bayes Classifier yielded an overall accuracy of 84.5%, with a precision of 85.2%, recall of 83.8%, and F1-score of 84.5%. The analysis suggests that shipping promotions are the main drivers of positive sentiment, while post-update app performance drops and payment errors trigger negative reviews.